THE MULTIPLE OCULAR MANIFESTATIONS OF A NEGLECTED NEWLY DIAGNOSED MULTIBACILLARY LEPROSY WITH GRADE II DISABILITY - Purnamasari, Suci; Sofia, Ovi (Majalah Oftalmologi Indonesia, 2025)
Introduction: Leprosy is a chronic granulomatous infection cause by Mycobacterium leprae that could involving the eye with prevalence within 51,6% to 85%. Despite the high prevalence of leprosy and ocular manifestation, ophthalmologist consultation is not routinely performed, thus leads to unrecognized ocular complications. This case report aims to portrays the ocular manifestation of multibacillary leprosy with grade II disability. Case report: A 71-year-old woman presented with severe corneal ulcer with perforation leading to the iris-lens prolapse resulted in total blindness of the left eye; peripheral ulcerative keratitis and neurotropic ulcer of the right eye; lagophthalmos, corneal hypoesthesia, and madarosis of both eye. The Dermatovenereology Department consultation revealed claw hand, ulnar nerve thickening on both upper extremity, and hypoesthesia on both upper and lower limb. The acid fast bacteria were identified from auricula skin scraping specimens with +3 bacterial index (BI) and 75% morphological index (MI). The patient was diagnosed with LE severe corneal ulcer with iris-lens prolapse, RE peripheral ulcerative keratitis (PUK) and neurotropic ulcer, RLE lagophthalmos, and multibacillary leprosy with grade II disability newly diagnosed. Left eye evisceration was performed after initiated the multidrug therapy (MDT) regiment. Conclusion: The ocular manifestation found in this case are corneal hypoesthesia, madarosis, corneal ulcer with perforation, iris-lens prolapse, peripheral ulcerative keratitis, and neurotropic ulcer. The management is directed to pathogen eradication and specific management on ocular manifestation. The collaboration with Dermatovenereology Department is required for comprehensive screening and management.